МОДЕЛЬ УЛЬТРАЗВУКОВЫХ ЭЛЕКТРОМЕХАНИЧЕСКИХ ПРИЕМНЫХ ПРЕОБРАЗОВАТЕЛЕЙ УЛЬТРАЗВУКОВЫХ ВОЛН РЕЛЕЯ - Мигущенко, Р.П.; Сучков, Г.М.; Петрищев, О.Н.; Ноздрачева, Е.Л. (Інститут електродинаміки НАН України, Київ, 2016)
The article deals with the model of the receiver high-frequency ultrasonic pulse Rayleigh waves that extending along the metal surface products. Application of such transducers allows to carry out operational control of large areas of products (sheets, large diameter pipes, a considerable number of other objects of the exploited). Highly efficient applying transducers of this type in the field of acoustic emission, especially in areas of high temperatures, radiation and other fields of information-measuring systems in the power industry, metallurgy, aggressive chemical production, transport, environmental segment. References 8, figures 5.